Genomic heritability and correlation between carcass traits in Japanese Black cattle evaluated under different ceilings of relatedness among individuals - Rostamzadeh Mahdabi, Elaheh; Tian, Rugang; Li, Yuan; Wang, Xiao; Zhao, Meng; Li, Hui; Yang, Ding; Zhang, Hao; Li, SuFan; Esmailizadeh, Ali (Frontiers in Genetics, 2023)
The investigation of carcass traits to produce meat with high efficiency has been in focus on Japanese Black cattle since 1972. To implement a successful breeding program in carcass production, a comprehensive understanding of genetic characteristics and relationships between the traits is of paramount importance. In this study, genomic heritability and genomic correlation between carcass traits, including carcass weight (CW), rib eye area (REA), rib thickness (RT), subcutaneous fat thickness (SFT), yield rate (YI), and beef marbling score (BMS) were estimated using the genomic data of 9850 Japanese Black cattle (4142 heifers and 5708 steers). In addition, we investigated the effect of genetic relatedness degree on the estimation of genetic parameters of carcass traits in sub-populations created based on different GRM-cutoff values. Genome-based restricted maximum likelihood (GREML) analysis was applied to estimate genetic parameters. Using all animal data, the heritability values for carcass traits were estimated as moderate to relatively high magnitude, ranging from 0.338 to 0.509 with standard errors, ranging from 0.014 to 0.015. The genetic correlations were obtained low and negative between SFT and REA (-0.198 (0.034)) and between SFT and BMS (-0.096 (0.033)) traits, and high and negative between SFT and YI (-0.634 (0.022)). REA trait was genetically highly correlated with YI and BMS (0.811 (0.012) and 0.625 (0.022), respectively). In sub-populations created based on the genetic-relatedness ceiling, the heritability estimates ranged from 0.212 (0.131) to 0.647 (0.066). At the genetic-relatedness ceiling of 0.15, the correlation values between most traits with low genomic correlation were overestimated while the correlations between the traits with relatively moderate to high correlations, ranging from 0.380 to 0.811, were underestimated. The values were steady at the ceilings of 0.30 to 0.95 (sample size of 5443 to 9850) for most of the highly correlated traits. The results demonstrated that there is considerable genetic variation and favorable genomic correlations between carcass traits. Therefore, the genetic improvement for the traits can be simultaneously attained through genomic selection. In addition, we observed that depending on the degree of relationship between individuals and sample size, the genomic heritability and correlation estimates for carcass traits may be different